2003
DOI: 10.1258/095646203321043228
|View full text |Cite
|
Sign up to set email alerts
|

'Shelf life' of <I>Trichomonas vaginalis</I>

Abstract: The diagnosis of Trichomonas vaginalis (TV) infection in women may be made by observing motile trichomonads in wet-mount preparations of vaginal discharge. The duration for which these organisms can be identified in such samples is unknown. We sought to assess this by performing wet-mount microscopy on samples from female patients immediately, and then in positive samples, every 10 minutes until motile trichomonads could no longer be identified. Of the 65 wet-mount specimens positive for TV, a cumulative total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…In some settings, the wet mount is transported to the microbiology laboratory and read by technicians after a significant time delay. The sensitivity of wet-mount microscopy for detecting T. vaginalis declines substantially with even relatively short time intervals between collection and examination (8). Where wet mount is available, the appropriate T. vaginalis test for wet-mount-negative subjects has not been delineated.…”
Section: Discussionmentioning
confidence: 99%
“…In some settings, the wet mount is transported to the microbiology laboratory and read by technicians after a significant time delay. The sensitivity of wet-mount microscopy for detecting T. vaginalis declines substantially with even relatively short time intervals between collection and examination (8). Where wet mount is available, the appropriate T. vaginalis test for wet-mount-negative subjects has not been delineated.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopy is unlikely to detect low level infections, in which the organism load in the sample may be under 10 4 cells/ml, and therefore will potentially not be included in the fields examined on the slide (Garber, 2005). The sensitivity of this method decreases rapidly if delays are present between sample acquisition and examination, with a reduction in sensitivity to 20% caused by a as little as a 10 minute delay reported (Kingston et al, 2003). Due to this it has been suggested that any diagnostic service which cannot guarantee the ability to test samples within an hour of acquisition should use alternative methods (Stoner et al, 2013).…”
Section: Diagnosis Female Patientsmentioning
confidence: 99%
“…The wet preparation should be read within 10 min of collection, as the trichomonads will quickly loose motility and be more difficult to identify. 25 The slide should be scanned, firstly at low magnification (100Â), and then at a higher magnification (400Â) to confirm the morphology of any trichomonads and to visualise the flagella. Microscopy as a diagnostic aid for TV has the advantage that it can be performed near to the patient and in a clinic setting.…”
Section: Laboratory Investigationsmentioning
confidence: 99%